2014
DOI: 10.1002/ajmg.a.36503
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenomic and phenotypic analysis in low‐level monosomy 7 mosaicism with non‐supernumerary ring chromosome 7

Abstract: We present the literature review of ring chromosome 7 and clinical, cytogenetic and fine molecular mapping of the first postnatal report of a male child with a non-supernumerary ring chromosome 7, r(7). The patient had dysmorphic features, developmental delay, dermatologic lesions with variable pigmentation, hypogenitalism, lumbar dextroscoliosis, cerebellar and ophthalmological abnormalities, and melanocytic congenital nevi. Cytogenetic analysis of peripheral blood and the nevus sample showed the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Analysis by SNP array showed a 0.8 Mb deletion in 7p22.3 (involving eight genes) and a 7.5 Mb deletion in 7q36 (involving 29 genes including some involved in genital and central nervous system development). As shown in Table 2, most of the deleted genes were involved in CNS, urogenital and M-S systems alterations associated with some of the clinical manifestations of the patient (Table 2) [21]. 2) Cytogenetic analysis identified three cell lines in different proportions in patient PM25: One with supernumerary marker chromosome, another with trisomy 14, and a normal cell line.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis by SNP array showed a 0.8 Mb deletion in 7p22.3 (involving eight genes) and a 7.5 Mb deletion in 7q36 (involving 29 genes including some involved in genital and central nervous system development). As shown in Table 2, most of the deleted genes were involved in CNS, urogenital and M-S systems alterations associated with some of the clinical manifestations of the patient (Table 2) [21]. 2) Cytogenetic analysis identified three cell lines in different proportions in patient PM25: One with supernumerary marker chromosome, another with trisomy 14, and a normal cell line.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of genomic regions was determined by decreases in the log R ratio. Mosaic proportions were estimated by B allele frequencies (BAF) [21, 22].…”
Section: Methodsmentioning
confidence: 99%
“…However, there remain a number of areas in the genome where the genotype‐phenotype correlation is not well described. Isolated 7p22.3p22.2 deletions have been rarely described; most reported cases involve either a much larger region of the 7p arm (Schomig‐Spingler, Schmid, Brosi, & Grimm, ; Speleman, Craen, & Leroy, ) or have an additional copy number variation which is larger in size and believed to be the greater contributor to the individual's clinical presentation (Kohannim, Peredo, Dipple, & Quintero‐Rivera, ; Salas‐Labadia et al, ; Schmidt, Udink ten Cate, WeiB, & Kochler, ). To date, there have only been two reports describing individuals with pure monosomy 7p22.3p22.2.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had demonstrated BRAF p.(V600E) mutations in single samples of CMN, with two reported cases of BRAF activation secondary to a chromosomal translocation involving 7q, demonstrated in melanocytes derived from the main CMN . Furthermore, multiple CMN is an established feature in patients with ring chromosome 7, with evidence of somatic mosaicism leading to significant gain of chromosome 7 within the CMN . However, a role for BRAF in CMN was debated, with no evidence for BRAF variants in true congenital naevi in one study .…”
mentioning
confidence: 99%
“…35 Furthermore, multiple CMN is an established feature in patients with ring chromosome 7, with evidence of somatic mosaicism leading to significant gain of chromosome 7 within the CMN. 42,43 However, a role for BRAF in CMN was debated, with no evidence for BRAF variants in true congenital naevi in one study. 27 A single case of multiple CMN where mutant BRAF was detected in more than one naevus from the same patient has now been published, 44 confirming clonality in that patient as opposed to a second hit, and effectively confirming the pathogenesis in previous reports of multiple CMN or CMN syndrome.…”
mentioning
confidence: 99%